La fórmula : ser-potencias-fines-valores-principios- normas-relaciones jurídicas - Riofrío Martínez Villalba, Juan Carlos (2016)
Fil: Riofrío Martínez Villalba, Juan Carlos. Universidad de Los Hemisferios; Ecuador